People of the Book? Responses to the Bible as 'Big Story' or 'Drama' - Hunt, Cherryl (The expository times, 2019)
Over recent decades there have been voices calling for a greater focus on communicating the Bible's 'big story', metanarrative, or 'drama' to ordinary Christians. It has been suggested that this will enable deeper engagement with the biblical texts, better interpretation and more adequate application including effective mission. To this end, a number of resources have been devised as vehicles by which the biblical story may be told. This paper examines responses to two of these resources, as they were used in small groups across a number of denominations and presents some suggestions for how to shape and deliver any such programme within churches.